Multiaxial Fatigue 1985
DOI: 10.1520/stp36220s
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Initiation and Growth in a High-Strength Ductile Steel Subject to In-Plane Biaxial Loading

Abstract: Flat cruciform-shaped specimens of HY100 steel were tested in fatigue under biaxial stress states. For Mode I crack growth, a tensile component of stress parallel to the crack decreased crack growth rate; a compressive component had the opposite effect. These changes in growth rate are explained in terms of the material's differing cyclic stress-strain response under shear and equibiaxial loading. Studies of Mode II growth were found difficult to perform, due to a critical balance between Mode I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
1
11
0
2
Order By: Relevance
“…Biaxial stress data falling away from this line would be expected to be significant. The present authors [6] have found results for normal or Mode I crack growth for A = -1 to fall to the left of Barsom's line for HYlOO steel as shown in Fig. 9.…”
Section: Presentation and Consideration Of Resultssupporting
confidence: 59%
“…Biaxial stress data falling away from this line would be expected to be significant. The present authors [6] have found results for normal or Mode I crack growth for A = -1 to fall to the left of Barsom's line for HYlOO steel as shown in Fig. 9.…”
Section: Presentation and Consideration Of Resultssupporting
confidence: 59%
“…Smith and Pascoe [22] suggested from biaxial fatigue tests on a HYlOO steel that the tensile stress component parallel to the crack surface decreased the mode I crack growth rate and the compressive component increased the fatigue crack growth rate. Moreover, the three stages of crack growth which could be observed in the behaviour of mode I crack growth seemed to vanish in mode I1 or mixed-mode crack growth.…”
Section: A Brief Historical Reviewmentioning
confidence: 99%
“…Smith (E.W.) and Pascoe [26,27] used a cruciform specimen to produce fully reversed mode I1 loading with a static mode I load, on HYlOO steel, a high yield, ductile, weldable steel. This static mode I load was different from the mode I load used by Smith (M.C.…”
Section: Experimental Workmentioning
confidence: 99%